PERBEDAAN SIKAP TERHADAP LAYANAN BIMBINGAN KONSELING ANTARA SISWA KELAS XI PROGRAM IPS DAN SISWA KELAS XI PROGRAM IPA SMA NEGERI I NGAWEN KABUPATEN BLORA - Johan Irawan; Anita Listiara (Faculty of Psychology, Diponegoro University, 2013)
Guidance and Counseling Services is an attempt to help the students in developing personal life, social life, learning activities, as well as planning and career development. Counseling services to facilitate the development of learners, individual, group and, according to the needs, potential, talents, interests, developments, potentials, and opportunities owned.The research subjects are as many as 180 people who were in class XI IPS 1, XI IPS 2, XI IPS 3, XI IPA 1, XI IPA 2, and XI IPA 3. Data collection was done by using a scale. The research involved 90 students and 90 students IPS IPA. The sampling technique used is taking the population as a whole using the techniques of Test-T. The research data was collected using psychological scales are scales BK attitudes toward service. Hypothesis testing was conducted using analysis of independent samples T-test.The data analysis methods of test T-test result mean IPS 180 students, 86 students whereas the mean value of 188.00 and the science of test results obtained by the value of t-test t = -3.618 at a significance level of 0.001 (p <0.05), this suggests that the hypothesis can be accepted, namely that the class XI students majoring in science have shown a positive attitude with a high mean, to use the service so that there are differences in attitudes BK to BK service between the two programs. Where the students of class XI science programs have more positive attitudes than students of class XI program IPS.